Experiência estética e o ensino de música: um estudo de caso da prática docente de um professor de uma escola pública do ensino fundamental no município de Maringá-PR - Silva, Rosangela Trabuco Malvestio da (Universidade Federal de São Carlos, 2020)
The objective of this study is to analyze the teaching of music in the art discipline in the early years of elementary school, highlighting the formative and aesthetic aspects, based on the theoretical framework of the Critical Theory authors. To carry out the work, readings and fictions from bibliographic sources performed were, as well as the analysis of the data collected by an empirical research carried out through the Objective Hermeneutic methodology. In order to reach the proposed objective, based on the authors of the Critical Theory, a bibliographical survey on music in the history of men performed was. Characterizing it in the context of today's society, its formative and/or deforming potential in the development of the thinking and aesthetic feeling of individuals highlighted was. Following, it discussed was about Art and Philosophy, with emphasis on aesthetic experience, relating it to the teaching of Art and Music in schools. For this, we used the postulates of the Critical Theory authors, so that it was possible an understanding about the theoretical conception approached in this work, which served as a contribution to the analysis during its development. Following, a history of art teaching in the country made was in order to understand and contextualize art in Brazilian schools, focusing on laws and official documents that support the Curriculum, the Pedagogical Political Project and the School Planning. Finally, a field research was carried out in an Elementary School - Early Years, of the Municipal Public Network of the city of Maringa-PR, in a fourth year class in the discipline of Art - among languages, music.The analysis of the data collected during the empirical research performed was carried out using the Objective Hermeneutic methodology. The didactics adopted in the classroom by “Teacher A” and the formative aspects of music lessons, were defined how two major categories. At the end of the study, after analyzing the data in the light of Critical Theory, it highlights some possibilities of an education for Emancipation in the teaching of Music. It should directed be to develop the aesthetic feeling in the elementary school students, acting against the values imposed by the capitalist society.
Aesthetic experience and music teaching: a case study of the teaching practice of a teacher from a public elementary school in the city of Maringá-PR
Keywords: Teoria crítica; Formação estética; Ensino de arte; Música; Hermenêutica objetiva; Escola pública; Critical theory; Aesthetic formation; Art teaching; Music; Objective hermeneutics; Public school; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM